The Role of The Pospay Application in Driving Digital Transformation of Services at The Post Office - Febrianto, Muhammad Rizky; Amanda, Dinda; Nursahidin, Nursahidin; Sutarjo, Moh. (Jurnal Polisci, 2025)
Background. This study was conducted with the aim of promoting the digital transformation of public services through the use of the Pospay application at the Sindanglaut Post Office. The Pospay application is one of the innovations created by PT. Pos Indonesia, designed to facilitate the public in conducting various digital transactions. Digital transformation is a strategic step in improving service quality, accelerating transaction processes, and expanding service reach to the public. However, its implementation at the Sindanglaut KCP Post Office still faces various challenges, such as insufficient information being provided to the public about the Pospay application, a limited understanding of technology among the public, particularly among the elderly, and system issues, including buffering or server disruptions. Aims. The research aims to evaluate the extent to which digital service innovations. Methods. Bill payments and money transfers are available on the Pospay app. Compared to conventional methods, the public's acceptance of this technology is notable. Conclusion. This is achieved through a participatory approach, direct mentoring, and social media platforms, such as Instagram. Using Everett M. Rogers' Innovation Diffusion Theory and providing solutions based on the theory's indicators—Relative Advantage, Compatibility, Complexity, Trialability, and Observability. Implementation. The study found improvements in all aspects except Complexity, where the public still perceives the app as too complicated to use. Thus, the app is not yet fully optimized.